Toddler Social Development Based on SKAP Data in West Java - Ade Saputra Nasution; Fitri Dian Nila Sari; Rindang Ekawati; Dadang Suhenda (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
The social development of toddlers has recently become important because it is a crisis period in the formation of the toddler's self-character when he grows up. The number of children a family has will be a challenge to form from the social development of the toddler itself. This study analyzes the influence of social development factors for toddlers. The data used is secondary data from SKAP 2019 West Java Province which was processed using chi-square to examine an effect between the independent variables (use of contraceptives, mother's education and ideal number of children) using a cross-sectional design with 2,803 respondents. Maternal education variable (0.000) <0.05 means that it has an influence on the social development of toddlers, the ideal number of children (0.003) <0.05 means that it has an influence on the social development of toddlers and the use of contraception (0.226) > 0.05 means that it has no effect with the social development of toddlers. Variable mother's education and the ideal number of children affect the development of toddlers in West Java Province. Keywords: contraceptive use, ideal number of children, mother's education, social development